Doctrine and Race : African American Evangelicals and Fundamentalism between the Wars - Mathews, Mary Beth Swetnam (Book collections on Project MUSE., 2017)
By presenting African American Protestantism in the context of white Protestant fundamentalism, Doctrine and Race: African American Evangelicals and Fundamentalism between the Wars demonstrates that African American Protestants were acutely aware of the manner in which white Christianity operated and how they could use that knowledge to justify social change. Mary Beth Swetnam Mathews's study scrutinizes how white fundamentalists wrote blacks out of their definition of fundamentalism and how blacks constructed a definition of Christianity that had, at its core, an intrinsic belief in racial equality. In doing so, this volume challenges the prevailing scholarly argument that fundamentalism was either a doctrinal debate or an antimodernist force. Instead, it was a constantly shifting set of priorities for different groups at different times. A number of African American theologians and clergy identified with many of the doctrinal tenets of the fundamentalism of their white counterparts, but African Americans were excluded from full fellowship with the fundamentalists because of their race. Moreover, these scholars and pastors did not limit themselves to traditional evangelical doctrine but embraced progressive theological concepts, such as the Social Gospel, to help them achieve racial equality. Nonetheless, they identified other forward-looking theological views, such as modernism, as threats to "true" Christianity. Mathews demonstrates that, although traditional portraits of "the black church" have provided the illusion of a singular unified organization, black evangelical leaders debated passionately among themselves as they sought to preserve select aspects of the culture around them while rejecting others. The picture that emerges from this research creates a richer, more profound understanding of African American denominations as they struggled to contend with a white American society that saw them as inferior. Doctrine and Race melds American religious history and race studies in innovative and compelling ways, highlighting the remarkable and rich complexity that attended to the development of African American Protestant movements. --